2023
DOI: 10.1111/nmo.14531
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychological well‐being: A novel concept for improving symptoms, quality of life, and health behaviors in irritable bowel syndrome

Abstract: Background: Though a growing body of research suggests that greater positive psychological well-being in irritable bowel syndrome (IBS) may be protective, existing brain-gut behavior therapies primarily target negative psychological factors. Little is known about how positive psychological factors in IBS relate to IBS symptoms, health-related quality of life (HRQoL), or adherence to key health behaviors, such as physical activity and diet modification. Accordingly, per the ORBIT model of behavioral treatment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
6
0
2
Order By: Relevance
“…This group of students showed greater symptom scores (19). Anxiety (20) and dietary behaviors (16,17) were often associated with GI symptoms, and positive psychological wellbeing and health behavior could moderate GI symptoms and result in a better QOL (21). Chinese undergraduate and postgraduate students have a heavier academic burden and poorer ability to regulate emotional and life stress than other groups, which may be the main reason for the lower QOL of these students.…”
Section: Discussionmentioning
confidence: 90%
“…This group of students showed greater symptom scores (19). Anxiety (20) and dietary behaviors (16,17) were often associated with GI symptoms, and positive psychological wellbeing and health behavior could moderate GI symptoms and result in a better QOL (21). Chinese undergraduate and postgraduate students have a heavier academic burden and poorer ability to regulate emotional and life stress than other groups, which may be the main reason for the lower QOL of these students.…”
Section: Discussionmentioning
confidence: 90%
“…Previous research have indicated that IBS is related to physical factors [20][21][22][23][24] . Patients with IBS who engage in more physical activity see a reduction in GI symptoms, most likely as a result of an increase in intestinal transit and the absorptive capacity of the gut 25 .…”
Section: Discussionmentioning
confidence: 99%
“…These factors may affect the pathogenesis of IBS via the brain-gut axis 3,21,35 . In addition, the majority of…”
Section: Discussionmentioning
confidence: 99%
“…Effective associations have been reported between screen time and sleep problems, depression, and psychological well-being 34 . These factors may affect the pathogenesis of IBS via the brain-gut axis 3 , 21 , 35 . Regarding the impact of IBS on sedentary behavior, many studies have found that the proportion of physical inactivity in IBS patients is higher, but few studies have determined that IBS is the cause of higher physical inactivity.…”
Section: Discussionmentioning
confidence: 99%